Effect of regional body composition changes on bone density remodeling after sleeve gastrectomy - Yang, Di; Xu, Rongrong; Tu, Yinfang; Xiao, Yunfeng; Zhang, Hongwei; Liu, Weijie; Zhang, Pin; Yu, Haoyong; Bao, Yuqian; Yang, Ying; Han, Junfeng (Frontiers in Endocrinology, 2023)
Background: Sleeve gastrectomy (SG) results in bone mineral density (BMD) loss and varying body composition parameters. However, the effects of body compositions on bone health are controversial. In order to accurately demonstrate their relationship and provide new insights into the causes of BMD loss after sleeve gastrectomy, this study is aimed to investigate the role of changes in body composition in BMD loss 12 months after SG. Methods: 41 Chinese individuals with obesity (25 women and 16 men) who underwent SG were prospectively examined for at least 12 months. Measurements of anthropometrics, body composition, BMD and blood samples were collected. Results: For 12 months, the femoral neck (FN) BMD and total hip (TH) BMD decreased significantly compared with baseline in both sexes but not lumbar spine (LS) BMD. Greater TH BMD loss was observed in men than in women. For the first 6 months post-SG, the FN BMD loss was positively associated with the estimated fat free mass index (eFFMI) reduction in women (adjusted β = 0.77, P = 0.004) and positively associated with reduction of subcutaneous fat area (SFA) in men (r = 0.931, P = 0.007). For 12 months post-SG, the FN BMD loss was negatively associated with visceral fat area (VFA) reduction in women (adjusted β = -0.58, P = 0.027) and men (adjusted β = -0.68, P = 0.032). TH BMD loss was positively associated with waist circumference reduction in women (r = 0.448, P = 0.028). Conclusion: FN and TH BMD decrease after SG in both women and men. The changes in body compositions are associated with BMD loss at different time points and bone sites. Our data emphasize the limitation of simply taking the total weight loss (% TWL) as an influencing factor of bone mineral density and the necessity of delineating body composition in relevant studies.